PENGARUH FAKTOR KEUANGAN DAN INTENSITAS ASET TETAP TERHADAP KEPUTUSAN PELAPORAN KEUANGAN DAN PAJAK - Ahmad Kamal Jama'; Harnovinsah Harnovinsah (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2017)
This study is purposed to test empirically the effect of debt ratio, long-term debt ratio, financing deficit and fixed assets intensity on financial and tax reporting decisions. Sampling using purposive sampling method and produces 101 manufacturing companies that listed on the Indonesia Stock Exchange during 2014 to 2016. Hypothesis testing using logistic regression analysis because independent variables measured by dummy. The results show that the debt ratio, long-term debt ratio and financing deficit give significant negative effect on the financial reporting and tax decisions. Meanwhile, fixed asset intensity does not give significant influence to financial reporting and tax decisions.